Measuring the operational impact of digitized hospital records: a mixed methods study. Issue 1 (December 2016) - Scott, Philip; Curley, Paul; Williams, Paul; Linehan, Ian; Shaha, Steven
Abstract Background Digitized (scanned) medical records have been seen as a means for hospitals to reduce costs and improve access to records. However, clinical usability of digitized records can potentially have negative effects on productivity. Methods Data were collected during follow-up outpatient consultations in two NHS hospitals by non-clinical observers using a work sampling approach in which pre-defined categories of clinician time usage were specified. Quantitative data was analysed using two-way ANOVA models and the Mann-WhitneyU test. A focus group was held with clinicians to qualitatively explore their experiences using digitized medical records. The quantitative and qualitative results were synthesized. Results Four hundred six consultations were observed. Using paper records, there was a significant difference in consultation times between hospitals (p  = 0.016) and a significant difference in consultation times between specialties within hospitals (p  = 0.003). Using digitized records there was a significant difference in consultation times between specialties within a hospital (p  = 0.001). Excluding outliers, there was no significant difference between consultation times using digitized records compared with consultations using paper records in the same hospital, either at site (p  > =0.285) or specialty level (p  > =0.122). With digitized records at site A, two out of three specialties showed a significant increase in time spent searching computer records (p  < =0.010, Δ = 01:50–07:10) and one specialty had a corresponding reduction in time spent searching paper records (p  = 0.015, Δ = −00:28). Site B showed a notable increase in direct patient care (p  < 0.001, Δ = 04:20–06:00) and time spent searching computer records (p  < =0.043, Δ = 00:10–01:40) and reductions in the other time categories. The focus group confirmed that the most recent clinical letter was a vital document in the patient record, often containing most of the required information. Concerns were expressed about consistency of scanning practice, causing uncertainty about what could be relied upon to exist in the digitized record. Benefits of digitized records included: access from multiple locations, better prepared ward rounds, improved inpatient handovers and an improved timeline of patient events. Limitations of digitized records included: increased complexity of creating a patient summary, display of specialised content such as hand-drawn diagrams, inability to quickly flick through the pages to find relevant content. Conclusions Digitized medical records can be implemented without detrimental operational impact. Inherent differences between specialties can outweigh the differences between paper and digitized records. Clear and consistent operational processes are vital for the reliability and usability of digitized medical records. Divergent views about usability (such as whether patient summary information is better or worse) may reflect familiarity with features of the digitized record.